PFRP structures under the predominately short term load - M.A. Salakhutdinov; L.R. Gimranov; I.L. Kuznetsov; A.E. Fakhrutdinov; L.M. Nurgaleeva (Inzhenerno-stroitelʹnyĭ zhurnal, 2020)
The subject of the study is a load bearing capacity of building structures from fiber reinforced polymer (FRP) shapes under the short term load, such as snow load and occupancy load, which significantly exceed values of dead load. Experimentally determined actual strength and stiffness under the short term load of following structural members and connections: of I-beams; bolted connections under the bearing load with different directions of material’s pultrusion relatively to applied force; connections transferring load via contact surfaces, at the ends of structural members, oriented normally to the direction of pultrusion; webs of the I-beams under locally applied load perpendicularly to the direction of pultrusion. Experimental studies deemed following results. Minimal flexural strength of beams obtained experimentally is on average 1.25 times higher than values of flexural strength determined theoretically. Strength of different types of connections obtained after testing procedures is on average 1.35–2.5 times higher of its theoretical values. Conducted studies allow widening of the field of an applicability of FRP profiles as structural members of small scale structures subjected to predominantly atmospheric or live loads, for instance, tiered and covered seating pavilion. Such types of structures subjected to short term load allow to utilize strength and stiffness of their structural members more deeply.